Electro-optically active ring devices for CMOS-compatible optoelectronics - Huang, Weibiao. (2013)
Lithium niobate (LiNbO3) has advantages of large electro-optic coefficients property and wide intrinsic bandwidth compared to traditional silicon as electro-optic material. A nested ring Mach–Zehnder interferometer (NR-MZI) intensity modulator on silicon-on-insulator has been proposed and investigated in this final year project.